Cellular Differences in the Cochlea of CBA and B6 Mice May Underlie Their Difference in Susceptibility to Hearing Loss - Liu, Huihui; Li, Gen; Lu, Jiawen; Gao, Yun-Ge; Song, Lei; Li, Geng-Lin; Wu, Hao (Frontiers in Cellular Neuroscience, 2019)
Hearing is an extremely delicate sense that is particularly vulnerable to insults from environment, including drugs and noise. Unsurprisingly, mice of different genetic backgrounds show different susceptibility to hearing loss. In particular, CBA/CaJ (CBA) mice maintain relatively stable hearing over age while C57BL/6J (B6) mice show a steady decline of hearing, making them a popular model for early onset hearing loss. To reveal possible underlying mechanisms, we examined cellular differences in the cochlea of these two mouse strains.Althoughthe ABR threshold and Wave I latency are comparable between them, B6 mice have a smaller Wave I amplitude. This difference is probably due to fewer spiral ganglion neurons found in B6 mice, as the number of ribbon synapses per inner hair cell (IHC) is comparable between the two mouse strains. Next, we compared the outer hair cell (OHC) function and we found OHCs from B6 mice arelarger in size but the prestin density is similar among them, consistent with the finding that they share similar hearing thresholds. Lastly, we examined the IHC functionand we found IHCs fromB6 mice have a larger Ca2+ current, release more synaptic vesiclesand recycle synaptic vesicles more quickly.Taken together, our results suggest that excessive exocytosis from IHCs inB6 micemay raise the probability of glutamate toxicity in ribbon synapses, which couldaccumulate over time and eventually lead to early onset hearing loss.